Coverage and Awareness of and Compliance with Mass Drug Administration for Elimination of Lymphatic Filariasis in Burdwan District, West Bengal, India (Journal of Health, Population and Nutrition, 2013)
India adopted WHOs strategy of repeated rounds of mass drug administration (MDA) with diethylcarbamazine to eliminate lymphatic filariasis. The present study attempted to assess the coverage and awareness of and compliance with MDA for elimination of lymphatic filariasis in Burdwan district of India, following MDA round in July 2010. A cross-sectional study was conducted among the four randomly-selected clusters in the district of Burdwan, West Bengal, India, covering 603 individuals from 154 households, using a predesigned pretested schedule. The drug distribution coverage, compliance, and effective coverage were 48.76 %, 70.07%, and 34.16% respectively. Only 41.4% of the study population was aware of the MDA activity. This evaluation study noted that MDA is restricted to tablet distribution only. There is an urgent need to improve compliance with drug intake through strengthening of the awareness programme involving both government health workers and community volunteers. J HEALTH POPUL NUTR 2013 Jun; 31(2): 171-177 DOI: http://dx.doi.org/10.3329/jhpn.v31i2.16380